2014
DOI: 10.1214/14-ejs972
|View full text |Cite
|
Sign up to set email alerts
|

Bootstrapping Aalen-Johansen processes for competing risks: Handicaps, solutions, and limitations

Abstract: Statistical inference in competing risks models is often based on the famous Aalen-Johansen estimator. Since the corresponding limit process lacks independent increments, it is typically applied together with Lin's (1997) resampling technique involving standard normal multipliers. Recently, it has been seen that this approach can be interpreted as a wild bootstrap technique and that other multipliers, as e.g. centered Poissons, may lead to better finite sample performances, see Beyersmann et al. (2013). Since … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 17 publications
(37 citation statements)
references
References 39 publications
1
36
0
Order By: Relevance
“…and Z 2n;i := X n;1;i 1(i ≤ n) + X n;2;i−n 1(i > n). That is, we obtain a linear weighted representation as in Dobler and Pauly (2014). Now replacing the i.i.d.…”
Section: The Data-dependent Multiplier Bootstrapmentioning
confidence: 99%
See 1 more Smart Citation
“…and Z 2n;i := X n;1;i 1(i ≤ n) + X n;2;i−n 1(i > n). That is, we obtain a linear weighted representation as in Dobler and Pauly (2014). Now replacing the i.i.d.…”
Section: The Data-dependent Multiplier Bootstrapmentioning
confidence: 99%
“…The variance n var( F 1 (t)) in the DDMB resampling version γ n is similar to the wild bootstrap variance estimator of Dobler and Pauly (2014), where we now use the same DDMB weights as in W D n . Again following Lin (1997) and Beyersmann et al (2013) we call the bands resulting from g 1 and g 2 equal precision and Hall-Wellner bands, respectively.…”
Section: Simultaneous Confidence Bands One-sample Tests and Confidenmentioning
confidence: 99%
“…These methods are compared in terms of the simulated coverage probabilities of the confidence bands described in Remark 4.4. We consider a simulation set-up motivated by Dobler and Pauly (2014), i.e. we chose the cause-specific hazard rates α 1 ptq " expp´tq and α 2 ptq " 1´expp´tq which yield the cumulative function of the first risk F 1 ptq " 0.5p1´expp´2tqq.…”
Section: Small Sample Behaviourmentioning
confidence: 99%
“…Now, to obtain a wild bootstrap version of this, we replace all martingale increments d M in the score function U n by ξ d N , with independent multipliers ξ for the counting processes of different individuals. Moreover, we replace in I n the counting processes d N with ξ 2 d N ; see Dobler and Pauly for a similar approach in the context of nonparametric cumulative incidence functions. It was shown that using these squared multipliers corresponds to using the optional variation process of the bootstrapped processes when considered as martingales in time .…”
Section: Methods For Confidence Interval Estimationmentioning
confidence: 99%